Peran Fiqih Muamalah Kontemporer dalam Perkembangan Bisnis Berbasis Syariah - Rhohis Kurniawan; Muhamad Zen (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
As the times develop, there will be many new things that emerge because humans will continue to innovate in line with the development of human thought, so to compensate and keep humans from running or getting out of their nature, religion is present to provide binding rules. The writing of this journal aims to find out the rules of contemporary muamalah fiqh as well as to find out what the role of contemporary muamalah fiqh is in the development of sharia-based businesses. The research methodology used in this research is descriptive qualitative research using the library study method (library research) Data collection in this study using the library study method related to theoretical studies and several references that will not be separated from scientific literature. The results of this study are an introduction to contemporary muamalah fiqh such as understanding, scope, rules of fiqh and the object of study of contemporary muamalah fiqh, as well as the role of contemporary muamalah fiqh in sharia-based business development.